BETWEEN MISSION AND MONEY: A LESSON LEARNED FROM SOCIAL ENTERPRISE IDENTITY - Wijayanti, Anita; Narsa, I Made (Jurnal Aplikasi Manajemen, 2023)
Social Entrepreneurship is a popular business model that proposes entrepreneurship to solve social and environmental problems by selling products or services. In Indonesia, the development of the number and awareness of entrepreneurs supported by the Social Entrepreneurship ecosystem is growing. However, due to the need for a unified definition of 'Social Entrepreneurship' and the slow pace of formal recognition from the government, organizations have developed with mixed practices and results. This study aims to describe the practice of Social Enterprise through the disclosure of corporate identity. Using Identity and Stakeholder Theory, this study explores the five characteristics of identity: mission, activity, governance, performance, and accountability. This multiple case study uses 10 Indonesian Social Enterprises. Data was collected through interviews and speeches in webinars coupled with documentation studies of uploaded narratives, photos, and videos on the company's official website, carried out from March to June 2023. Data analysis uses Nvivo to find themes from various Social Enterprise identity criteria groups. The results show that Social Enterprise has a unique mission and activities that carry a social value where community, empowerment, welfare and sustainability are more emphasized than profit. Institutional commitment as a Social Enterprise is proven by disclosing the impact achieved through impact reports, impact achievement profiles, SDG achievements, or articles in the news column. However, Financial performance is rarely disclosed, even though several companies have disclosed the distribution of their profits. Accountability practice in formal and informal to its stakeholder. This study provides guidelines for how companies disclose and be accountable for their identity as a Social Enterprise.